Case series of cutaneous T‐cell lymphomas treated with bexarotene‐based therapy. Issue 6 (24th March 2020) - Fujimura, Taku; Sato, Yota; Tanita, Kayo; Amagai, Ryo; Shimauchi, Takatoshi; Ogata, Dai; Fukushima, Satoshi; Miyashita, Azusa; Fujisawa, Yasuhiro; Kambayashi, Yumi; Aiba, Setsuya
Abstract: Bexarotene is useful for both early and advanced cutaneous T‐cell lymphoma (CTCL), and is sometimes applied to ultraviolet‐tolerant early CTCL patients as one of the first‐line therapies in the real world. However, continuous administration of bexarotene is sometimes difficult because of its adverse events (AE). Development of an appropriate protocol for bexarotene that can induce a consistent response for CTCL without severe AE (SAE) is needed. We retrospectively investigated 29 Japanese cases of CTCL and evaluated the efficacy of treatment and incident ratios of all AE and SAE. Objective response rate (ORR) for the overall cohort was 65.5%. ORR of the 300 mg/m 2 cohort (conventional dose) was 76.2%, while that of the 150–300 mg/body (low dose) with narrowband ultraviolet B light (NBUVB) cohort was 37.5%. Mean event‐free survival was 10.0 months for all patients, 6.7 months for the bexarotene conventional‐dose cohort and 19.1 months for the low‐dose with NBUVB cohort. The incident ratio of total SAE for all patients was 20.7%. The incident ratio of total SAE was 23.8% for the conventional‐dose cohort and 12.5% for the low‐dose with NBUVB cohort. Our present study suggests that low‐dose bexarotene plus NBUVB therapy is well‐tolerated and could be one of the optimal therapies for advanced CTCL.